2021
DOI: 10.1097/acm.0000000000004022
|View full text |Cite
|
Sign up to set email alerts
|

Who Is Caring for Health Care Workers’ Families Amid COVID-19?

Abstract: Amid the COVID-19 pandemic, women in medicine, including faculty, residents, medical students, and other health care workers (HCWs), are facing unparalleled challenges. The burdens of pandemic-associated increases in domestic and caregiving responsibilities, professional demands, health risks associated with contracting COVID-19, and the resulting psychosocial distress have exacerbated existing gender disparities at home, at work, and in academia. School and day care closures have created additional childcare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 13 publications
2
27
0
Order By: Relevance
“…To make matters worse, early career women were more likely to have concerns that the pandemic would impact future job promotions and fear institutional retribution if they were to request a leave of absence or a tenure clock extension. These data contribute to the opinion pieces that have outlined an increased impact of the pandemic on women and support those that are sounding alarms that women in academic medicine are facing a crisis [ 28 , 31 , 35–39 ], as well as supports data recently published by the NIH that early-career faculty are more concerned about the impact of the pandemic on their career trajectory [ 46 ].…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…To make matters worse, early career women were more likely to have concerns that the pandemic would impact future job promotions and fear institutional retribution if they were to request a leave of absence or a tenure clock extension. These data contribute to the opinion pieces that have outlined an increased impact of the pandemic on women and support those that are sounding alarms that women in academic medicine are facing a crisis [ 28 , 31 , 35–39 ], as well as supports data recently published by the NIH that early-career faculty are more concerned about the impact of the pandemic on their career trajectory [ 46 ].…”
Section: Discussionsupporting
confidence: 74%
“…The present study found that women were more likely to be responsible for childcare following the closure of these schools due to the pandemic. Overall, faculty felt negatively impacted by these increased childcare responsibilities, as predicted by Robinson and colleagues [ 31 ] Childcare can be cost prohibitive, which may explain the significant negative impact we found early career faculty felt compared to other career levels, and it is not offered at night and on weekends, which also may explain the significant negative impact we found clinical faculty felt compared to non-clinical faculty. Additionally, clinical shifts increased as a result of the overburdened healthcare system at the onset of the pandemic and continue to be full as health-care workers see patients who may have put off care throughout the pandemic.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Taken in conjunction, these findings suggest many mothers have withdrawn from the workforce to some extent, likely as a result of increasing caretaking responsibilities. As Robinson, Engelson, and Hayes [ 199 ] argued with reference to childcare issues faced by workers in the healthcare sector, “This poses incalculable risks to families, science, and society.”…”
Section: Organization Of Workmentioning
confidence: 99%
“…Taken in conjunction, these findings suggest many mothers have withdrawn from the workforce to some extent, likely as a result of increasing caretaking responsibilities. As Robinson, Engelson, and Hayes [199] argued with reference to childcare issues faced by workers in the healthcare sector, "This poses incalculable risks to families, science, and society." According to data from the Substance Abuse and Mental Health Services Administration (SAMHSA), mental health issues have been increasing for several years among USA adults before the pandemic.…”
Section: Pandemic Trendsmentioning
confidence: 99%